2018
DOI: 10.1186/s40795-018-0253-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of whole milk compared to skim milk and apple juice consumption in breakfast on appetite and energy intake in obese children: a three-way randomized crossover clinical trial

Abstract: Background: A limited number of studies have examined the effect of dairy on satiety and short-term energy intake among children; furthermore we are not aware of any study comparing high and low-fat dairy products regarding their effect on appetite and short-term energy intake. Our objective was to assess the effect skim milk (SM) compared to whole milk (WM) and apple juice (AJ) on satiety and energy intake at lunch among 10-12 y children with obesity. Methods: Fifty children with obesity who aged 10-12 y were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Consumption of whole-fat dairy products rather than reduced-fat varieties could result in increased feelings of satiety. In a randomized crossover trial, 48 Iranian children consumed a breakfast with either skim milk or whole-fat milk for 2 d ( 80 ). Children reported a higher satiety score 4 h after drinking whole-fat milk with breakfast compared with skim milk.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of whole-fat dairy products rather than reduced-fat varieties could result in increased feelings of satiety. In a randomized crossover trial, 48 Iranian children consumed a breakfast with either skim milk or whole-fat milk for 2 d ( 80 ). Children reported a higher satiety score 4 h after drinking whole-fat milk with breakfast compared with skim milk.…”
Section: Discussionmentioning
confidence: 99%
“…In another study comprising 48 obese children (mean age 11 years), girls reported higher satiety scores 4 h after drinking whole cow's milk compared with skimmed milk, and low-fat cow's milk significantly reduced appetite compared with apple juice 2 h after consumption. These differences, however, did not translate to changes in energy intake at an ad libitum lunchtime meal across all conditions in girls, boys and the group as a whole (108) . As mentioned, only one investigation (comprising two experiments) has sought to establish the effect of cow's milk (and other dairy products) on appetite and feeding behaviour in normal weight and overweight/obese children (mean age 11.5 years), where subjective appetite and appetite-related analytes were measured (112) .…”
Section: Appetite Regulationmentioning
confidence: 69%
“…From the available studies (108)(109)(110)(111)(112) , cow's milk has principally been given as a mid-morning snack or alongside breakfast, with the volume of cow's milk offered to children ranging from 160 ml to 250 ml. Based on these studies, the evidence concerning cow's milk and appetite regulation is inconclusive.…”
Section: Appetite Regulationmentioning
confidence: 99%
“…It contains high nutritional quality protein and other naturally present high bioavailable bioactive components, minerals (mainly calcium), and fat-soluble vitamins (mainly vitamins D and A) [ 23 ]. Evidence consistently shows that daily cow’s milk consumption improves the intake of energy, protein, vitamins, and minerals [ 28 ], hydration, dental and bone health, and growth; furthermore, there is increasing evidence of the effect of cow’s milk on appetite regulation and satiety that may reduce energy intake in overweight or obese children [ 29 , 30 , 31 , 32 , 33 ]. Therefore, it is advisable to promote the consumption of cow’s milk by children to improve their health.…”
Section: Discussionmentioning
confidence: 99%